INVESTIGATION OF LOGGING REMAINS AS FUEL - Kondratjevs, Viktors; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Nowadays in Latvia is imported large quantity of fuel to meet the needs of consumers. At the same time local biofuel is left on the areas of the forest. This material is possible to be recycled into wood chips to use it effectively for producing energy. It was analyzed sources of literature to perform conclusions about the characteristics of forest logging and ways of recycling. To assess the quality of wood chips taken the examples. The following measurements stated in the laboratory: the calorific value, carbon content and moisture. In Latvia’s territory the remains of logging are available in great amounts, it is possible to convert them into wood chips. The energetic features of the wood chips are high enough to use it for producing energy in the cogeneration plants.